First outbreak of Oropouche Fever reported in a non-endemic western region of the Peruvian Amazon: Molecular diagnosis and clinical characteristics - Silva-Caso W. (2019)
Oropouche fever is an under-reported and emerging infectious disease caused by Oropouche virus (OROV). Its incidence is under-estimated mainly due to clinical similarities with other endemic arboviral diseases and the lack of specific diagnostic tests. We report the first outbreak of Oropouche fever in a western region of the Peruvian Amazon in Huanuco, Peru.